QSAR, docking studies of 1, 3-thiazinan-3-yl isonicotinamide derivatives for antitubercular activity. (June 2017) - Chitre, Trupti S.; Asgaonkar, Kalyani D.; Patil, Shital M.; Kumar, Shiva; Khedkar, Vijay M.; Garud, Dinesh R.
Graphical abstract: Highlights: Design of new chemical entities of 1, 3 thiazinan – Isoniazid. Combilib and absorption, distribution, metabolism excretion (ADME) predictions. Docking studies with enoyl ACP reductase. Abstract: The enzyme – enoyl acyl carrier protein reductase (enoyl ACP reductase) is a validated target for antitubercular activity. Inhibition of this enzyme interferes with mycolic acid synthesis which is crucial for Mycobacterium tuberculosis cell growth. In the present work 2D and 3D quantitative structure activity relationship (QSAR) studies were carried out on a series of thiazinan–Isoniazid pharmacophore to design newer analogues. For 2D QSAR, the best statistical model was generated using SA-MLR method ( r 2 = 0.958, q 2 = 0.922) while 3D QSAR model was derived using the SA KNN method ( q 2 = 0.8498). These studies could guide the topological, electrostatic, steric, hydrophobic substitutions around the nucleus based on which the NCEs were designed. Furthermore, molecular docking was performed to gauze the binding affinity of the designed analogues for enoyl ACP reductase enzyme. Amongst all the designed analogues the binding energies of SKS 01 and SKS 05 were found to be −5.267 kcal/mol and −5.237 kcal/mol respectively which was comparable with the binding energy of the standard Isoniazid (−6.254 kcal/mol).